Glass, preparation method and application

By optimizing the components and processes of aluminosilicate glass, the problem of insufficient strength in traditional glass at low thickness is solved, and the effects of high strength, deformation resistance and scratch resistance are achieved, meeting the application needs of smart terminals and automotive glass.

CN119774873AInactive Publication Date: 2025-04-08HEBEI ANGRUI AUTOMATION EQUIPMENT TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411915144.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional soda-lime silicone glass cannot meet the requirements of high strength, high deformation resistance and scratch resistance at low thickness, and it is difficult to meet the needs of applications such as smart terminal display screens and automotive protective glass.

Method used

Using an aluminosilicate glass, its components include silica, alumina, boron oxide, sodium oxide, potassium oxide and magnesium oxide, through specific weight relationships and chemical reinforcement processes, the grid structure and surface stress layer of the glass are optimized, and its mechanical strength and scratch resistance are improved.

Benefits of technology

The stress strength, stress depth and hardness of the glass are significantly improved at low thickness, enhanced its impact and scratch resistance, and met the needs of applications such as smart terminal display screens and automotive protective glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses glass, a preparation method and application, and relates to the technical field of glass manufacturing. Wherein the glass comprises the following components: silicon dioxide, aluminum oxide, boric oxide, sodium oxide, potassium oxide and magnesium oxide; the weight relationship between silicon dioxide and aluminum oxide satisfies a specific quantitative relationship, and the weight relationship between aluminum oxide, boron oxide and magnesium oxide satisfies a specific quantitative relationship. The prepared glass has high stress intensity and stress depth, and the scratch resistance and impact resistance of the glass enable the glass to meet the requirements of display equipment of an intelligent terminal and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass manufacturing technology, and in particular to a type of glass, a preparation method thereof, and its applications. Background Technology

[0002] In recent years, with the increasing popularity of smart terminals such as mobile phones and tablets, and their trend towards thinner and lighter designs, the thickness of display components such as screens in these smart devices has been continuously reduced. However, this leads to a problem: the strength of the glass decreases as the thickness decreases. Furthermore, traditional soda-lime-silica glass cannot simultaneously meet the requirements of high strength, high deformation resistance, and scratch resistance at low thicknesses. Therefore, it is necessary to develop a type of glass that possesses high strength and high hardness at low thicknesses to meet these requirements. Summary of the Invention

[0003] The main objective of this invention is to develop a glass, a preparation method, and an application that achieves sufficient strength and hardness at a relatively low thickness to meet the requirements of applications such as smart terminal displays, automotive protective glass, and automotive windows.

[0004] To achieve the above objectives, the present invention provides a glass comprising, by weight percentage: silicon dioxide: 61–66 wt%; aluminum oxide: 12–20 wt%; boron oxide: 2–5 wt%; sodium oxide: 10–16 wt%; potassium oxide: 0.5–3 wt%; magnesium oxide: 0.5–4 wt%; wherein the weight relationship between silicon dioxide and aluminum oxide satisfies: 9.91 ≤ 0.31SiO2 - 0.45Al2O3 ≤ 15.06; and / or the weight relationship between aluminum oxide, boron oxide, and magnesium oxide satisfies: 0.34 ≤ (1.35B2O3 + 0.72MgO) / 0.45Al2O3 ≤ 1.78.

[0005] In one embodiment, the weight relationship between silicon dioxide and aluminum oxide in the glass composition satisfies: 13.44 ≤ 0.31SiO2 - 0.45Al2O3 ≤ 15.06.

[0006] In one embodiment, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide satisfies: 1.13≤(1.35B2O3+0.72MgO) / 0.45Al2O3≤1.78.

[0007] In one embodiment, the weight relationship between silicon dioxide and aluminum oxide in the glass composition satisfies: 9.91≤0.31SiO2-0.45Al2O3≤12.35.

[0008] In one embodiment, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide in the glass composition satisfies: 0.34 ≤ (1.35B2O3 + 0.72MgO) / 0.45Al2O3 ≤ 0.84.

[0009] In one embodiment, the annealing temperature T of the glass a Glass transition temperature T g and strain temperature T st The following relationship must be satisfied: 1.65 ≤ (T) a -T st ) / (T a -T g ≤3.5.

[0010] In one embodiment, the melting temperature T of the glass m The temperature ranges from 1520 to 1600℃.

[0011] In one embodiment, the annealing temperature T of the glass a >570℃.

[0012] In one embodiment, the glass transition temperature T of the glass is... g ≥550℃; In one embodiment, the strain temperature Tst of the glass is ≥535°C.

[0013] In one embodiment, when the thickness of the glass is 0.5~0.6mm, the stress intensity CS value of the glass is 903~942MPa; In one embodiment, when the thickness of the glass is 0.5~0.6 mm, the stress layer depth (DOL) of the glass is 39.8~45.1 μm; In one embodiment, when the thickness of the glass is 0.5 to 0.6 mm, the Vickers hardness value of the glass is 710 to 747 HV.

[0014] The present invention also proposes a method for preparing glass, the method comprising the following steps: S10. Mix, melt, clarify, homogenize, shape, and anneal the components in the raw materials according to the proportions to obtain intermediate glass products; S20. Cut the intermediate glass product obtained in step S10 to obtain an intermediate glass plate; control the thickness of the intermediate glass plate to be 0.02~0.6mm. S30. The glass plate intermediate obtained in step S20 is chemically strengthened to obtain the glass.

[0015] In one embodiment, the clarifying agent in step S10 includes at least one of sodium chloride, sodium sulfate, and cerium oxide.

[0016] In one embodiment, in the clarification process of step S10, the amount of clarifying agent used is 0.3 to 0.6 wt% of the glass.

[0017] In one embodiment, the chemical strengthening in step S30 specifically includes: The intermediate glass plate obtained in step S20 is kept at 270~320℃ for 30~50 minutes. Then, the intermediate glass plate after heat preservation is placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400~430℃ and the chemical strengthening time is controlled at 0.25~4 hours.

[0018] In one embodiment, the molten salt comprises 0-1 wt% NaNO3 and 99-100 wt% KNO3.

[0019] The present invention also proposes a display device that utilizes the glass.

[0020] The technical solution of this invention provides a composition and specific ratio of aluminosilicate glass. By rationally controlling the proportion of [AlO4] tetrahedral structure and other components such as boron oxide and magnesium oxide in the glass system through a specific weight relationship, the network structure in the glass phase is strengthened. This invention also achieves a higher annealing temperature T by rationally controlling the composition and specific ratio of the aluminosilicate glass. a Strain temperature T st and glass transition temperature T g This invention further enhances the stress intensity and stress depth of the glass by satisfying specific quantitative relationships. In the preparation method, the pretreatment and chemical strengthening process promotes rapid ion exchange on the glass surface and achieves a certain stress layer depth, thereby further enhancing the stress intensity and stress depth of the glass, and thus improving the scratch resistance and impact resistance of the glass. Detailed Implementation

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.

[0023] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.

[0024] The technical problem addressed by this application is that, with the increasing popularity of smart terminals such as mobile phones and tablets, and their trend towards thinner and lighter designs, the thickness of display components, such as screens, in these smart devices is required to continuously decrease. However, this leads to a problem where the strength of the glass decreases as the thickness decreases. Furthermore, traditional soda-lime silica glass cannot simultaneously meet the requirements of low thickness, high strength, high deformation resistance, and scratch resistance.

[0025] To address the aforementioned technical problems, this invention proposes a glass with strength and hardness at low thickness that can meet the requirements of glass materials for smart terminal displays, automotive protective glass, and automotive windows. The invention also proposes a glass, a preparation method, and an application.

[0026] This invention proposes a glass comprising, by weight percentage: silicon dioxide: 61-66 wt%; aluminum oxide: 12-20 wt%; boron oxide: 2-5 wt%; sodium oxide: 10-16 wt%; potassium oxide: 0.5-3 wt%; magnesium oxide: 0.5-4 wt%; wherein the weight relationship between silicon dioxide and aluminum oxide satisfies: 9.91 ≤ 0.31SiO2 - 0.45Al2O3 ≤ 15.06; optionally, the weight relationship between aluminum oxide, boron oxide, and magnesium oxide satisfies: 0.34 ≤ (1.35B2O3 + 0.72MgO) / 0.45Al2O3 ≤ 1.78.

[0027] It should be noted that the silica content in the glass is 61-66 wt%, which can be 61 wt%, 61.5 wt%, 63 wt%, 64 wt%, 65.5 wt%, 66 wt%, or more, including but not limited to the values ​​listed above. Glass made within this content range has a suitable coefficient of thermal expansion and mechanical strength. This is because silica is the basic component that constitutes the glass network structure, namely the silicon-oxygen tetrahedral [SiO4] main network structure. The silicon-oxygen tetrahedral [SiO4] main network structure enables the glass to form a continuous network structure, which can affect the glass's chemical stability, mechanical strength, viscosity in the molten state, optical properties, and other basic properties through ion exchange with the outside world.

[0028] It should also be noted that the content of alumina in the glass is 12-20 wt%, which can be 12 wt%, 12.6 wt%, 13.8 wt%, 15.3 wt%, 18.1 wt%, 20 wt%, or more, including but not limited to the values ​​listed above. Within this content range, the aluminum-oxygen tetrahedron [AlO4] formed by Al in alumina and non-bridging oxygen forms a tetrahedron connected to the silicon-oxygen tetrahedron [SiO4], making the broken network complete. This can improve the cross-linking degree of the glass network structure, thereby improving the mechanical strength and chemical stability of the glass. The aluminum-oxygen tetrahedron [AlO4] has a larger volume than the silicon-oxygen tetrahedron, creating larger gaps in the glass structure, which is conducive to ion exchange, thereby improving the scratch resistance and drop resistance of the glass. Excessive alumina will form two structures: aluminum-oxygen tetrahedra [AlO4] and aluminum-oxygen octahedra [AlO6]. The aluminum-oxygen octahedra [AlO6] act as network exogens, remaining free within the network structure and not participating in cross-linking. However, an increase in the number of aluminum-oxygen octahedra [AlO6] will increase the proportion of bridging oxygen, thus affecting the chemical stability of the glass. Furthermore, if the Al2O3 content is too low, the glass is prone to crystallization, has low mechanical strength, and is also unfavorable for forming.

[0029] It should also be noted that the boron oxide content in the glass is 2-5 wt%, which can be 2 wt%, 2.5 wt%, 3.2 wt%, 3.5 wt%, 4.3 wt%, 5 wt%, or more, including but not limited to the values ​​listed above. Within this content range, boron oxide tends to form [BO3] tricoordinate structural units. This structure can break the strong connection between silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra, making the network structure looser. It can better adapt to volume changes during cooling, thereby reducing potential cracks, which is beneficial for lowering the melting point of the glass and increasing its toughness. Moreover, the tricoordinate boron-oxygen bond is stronger than the tetracoordinate boron-oxygen bond and is not easily attacked and destroyed by water molecules, thereby improving the chemical stability of the glass.

[0030] It should also be noted that the sodium oxide content in the glass is 10-16 wt%, which can be 10 wt%, 11.3 wt%, 13.2 wt%, 14.8 wt%, 15.3 wt%, 16 wt%, or more, including but not limited to the values ​​listed above. Within this content range, sodium oxide, as a network exogenous substance, is one of the main exchange ions in the chemical strengthening process, and mainly plays the role of fluxing, improving processability, and adjusting the coefficient of expansion.

[0031] It should also be noted that the content of potassium oxide in the glass is 0.5-3 wt%, which can be 0.5 wt%, 1.2 wt%, 1.5 wt%, 2 wt%, 2.3 wt%, 3 wt%, etc., including but not limited to the values ​​listed above. Within this content range, potassium oxide can also adjust the high-temperature viscosity of the glass during melting and the mechanical strength after forming. However, unlike sodium oxide, potassium oxide does not participate in the ion exchange process, and potassium oxide will cause the thermal expansion coefficient of the glass to increase. Therefore, the amount of potassium oxide used needs to be controlled.

[0032] It should also be noted that the content of magnesium oxide in the glass is 0.5 to 4 wt%, which can be 0.5 wt%, 1.1 wt%, 2 wt%, 2.9 wt%, 3.3 wt%, 4 wt%, and other values, including but not limited to the values ​​listed above. Within this content range, the main function of magnesium oxide is to lower the melting point of the glass and promote the melting of the glass. If the content is less than 0.5 wt%, it cannot significantly improve the melting effect of the glass. If the content is greater than 4 wt%, the aluminosilicate glass is prone to devitrification.

[0033] It should also be noted that the weight relationship between silicon dioxide and aluminum oxide satisfies: 9.91≤0.31SiO2-0.45Al2O3≤15.06. In this invention, both silicon dioxide and aluminum oxide participate in the formation of the glass grid structure in a three-dimensional tetrahedral structure. By limiting the above quantitative relationship, the quantities of the two basic components constituting the main body of the grid in the glass structure can reach a special balance, which can prevent the appearance of a high proportion of six-coordinate aluminum-oxygen octahedrons in the glass structure, thereby affecting the mechanical strength of the glass, such as stress intensity, stress depth, and hardness.

[0034] It should also be noted that the weight relationship of the aluminum oxide, boron oxide, and magnesium oxide satisfies: 0.34 ≤ (1.35B₂O₃ + 0.72MgO) / 0.45Al₂O₃ ≤ 1.78. In this invention, boron oxide, as a network modifier, can introduce tricoordinate [BO₃], which, although weakening the strength of the glass network, can also improve the thermal stability and chemical durability of the glass. Magnesium oxide, as an alkaline earth metal oxide, mainly exists in an octahedral structure and also plays a role in network modification, which can enhance the mechanical strength of the glass and adjust the coefficient of thermal expansion of the glass. By controlling the quantitative relationship between aluminum oxide as a network form and boron oxide and magnesium oxide as modifiers to achieve a special balance, the stability and strength of the glass network structure can be ensured, and the glass can be prevented from becoming too brittle or having too low a melting point due to excessive modifiers.

[0035] In one embodiment, the weight relationship between silicon dioxide and aluminum oxide in the glass composition satisfies: 13.44 ≤ 0.31SiO2 - 0.45Al2O3 ≤ 15.06; glass of corresponding thickness obtained within this range has higher stress strength, stress depth and hardness.

[0036] In one embodiment, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide in the glass composition satisfies: 1.13 ≤ (1.35B2O3 + 0.72MgO) / 0.45Al2O3 ≤ 1.78; the glass of the corresponding thickness obtained within this range has higher stress strength, stress depth and hardness, while also giving the glass better melting properties.

[0037] In one embodiment, the weight relationship between silicon dioxide and aluminum oxide in the glass composition satisfies: 9.91≤0.31SiO2-0.45Al2O3≤12.35; glass of corresponding thickness obtained within this range has higher stress strength, stress depth and hardness.

[0038] In one embodiment, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide in the glass composition satisfies: 0.34 ≤ (1.35B2O3 + 0.72MgO) / 0.45Al2O3 ≤ 0.84; the glass of the corresponding thickness obtained within this range has higher stress strength, stress depth and hardness, while also giving the glass better melting properties.

[0039] In one embodiment, the annealing temperature T of the glass a Glass transition temperature T g and strain temperature T st The following relationship must be satisfied: 1.65 ≤ (T) a -T st ) / (T a -T g≤3.5. It should be noted that, based on the aforementioned quantitative relationships of the corresponding component contents, the annealing temperature T of the glass is further limited. a Glass transition temperature T g and strain temperature T st It can further improve the stress strength and stress depth of the glass obtained after chemical strengthening.

[0040] In one embodiment, the melting temperature T of the glass m The temperature ranges from 1520 to 1600°C. The glass used in this invention is aluminosilicate glass, which has a higher melting temperature than soda-lime glass and borosilicate glass due to its higher proportion of alumina.

[0041] In one embodiment, the annealing temperature T of the glass a >570℃. It should be noted that annealing temperatures are generally applicable to aluminosilicate glass, borosilicate glass, or other specialty glasses with high glass transition temperatures. This temperature range is chosen to ensure that the glass can fully release internal stress during annealing, while avoiding softening or deformation due to excessively high temperatures. Selecting a suitable annealing process is crucial for the mechanical strength, thermal stability, and optical properties of the glass.

[0042] In one embodiment, the glass transition temperature T of the glass is... g ≥550℃.

[0043] In one embodiment, the strain temperature T of the glass st ≥535℃.

[0044] The present invention also provides a method for preparing the glass, comprising the following steps: S10. Mix, melt, clarify, homogenize, shape, and anneal the components in the raw materials according to the proportions to obtain intermediate glass products; S20. Cut the intermediate glass product obtained in step S10 to obtain an intermediate glass plate; control the thickness of the intermediate glass plate to be 0.02~0.6mm. S30. The glass plate intermediate obtained in step S20 is chemically strengthened to obtain the glass.

[0045] In one embodiment, the clarifying agent in step S10 includes at least one of sodium chloride, sodium sulfate, and cerium oxide.

[0046] In one embodiment, in the clarification process of step S10, the amount of clarifying agent used is 0.3 to 0.6 wt% of the glass.

[0047] In one embodiment, the chemical strengthening in step 30 specifically includes: placing the intermediate glass plate obtained in step 20 at 270~320℃ for 30~50 minutes, and then placing the intermediate glass plate after heat treatment in molten salt for chemical strengthening treatment, controlling the chemical strengthening temperature at 400~430℃ and controlling the chemical strengthening time at 0.25~4 hours.

[0048] It should be noted that the heat insulation treatment before chemical strengthening makes the temperature distribution of the glass more uniform, avoiding stress concentration caused by local temperature differences; it also makes it easier for sodium ions on the glass surface to be displaced, thereby increasing the depth and efficiency of ion exchange. This helps to increase the thickness of the compressive stress layer on the glass surface, enhancing its impact resistance.

[0049] In one embodiment, the molten salt comprises 0-1 wt% NaNO3 and 99-100 wt% KNO3.

[0050] In one specific embodiment, the method for preparing the glass includes the following steps: S10. Calculate the required raw materials according to the designed glass composition, mix them evenly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, using a 1:1 weight ratio of NaNO3 and CeO2, with the clarifying agent added at 0.5 wt% of the raw materials. Heat at 1520–1600℃ for 7 hours and mix evenly. Remove the crucible, pour the molten glass into a preheated mold, and cast it into blocks. Place the formed glass blocks in a muffle furnace and hold at the annealing temperature for 2 hours. Cool to room temperature and remove. S20. Cut the intermediate glass product obtained in step S10 to obtain an intermediate glass plate; control the thickness of the intermediate glass plate to be 0.02~0.6mm. S30. The intermediate glass plate obtained in step S20 is kept at 270~320℃ for 30~50 minutes. Then, the intermediate glass plate after heat preservation is placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400~430℃ and the chemical strengthening time is controlled at 0.25~4 hours. The molten salt includes 0~1wt% NaNO3 and 99~100wt% KNO3.

[0051] It should be noted that the above description of the preparation method is only used to explain the content of the present invention and does not limit the scope of protection of the present invention.

[0052] Furthermore, the present invention also proposes a display device that utilizes the aforementioned glass. After applying the glass, the display device exhibits better drop resistance, impact resistance, and scratch resistance.

[0053] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.

[0054] Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this application are commercially available, and the methods used are conventional methods in the art.

[0055] Relevant testing methods: (1) Determination of surface stress intensity CS value and surface stress depth DOL value: The surface stress was measured on the glass prepared in each example and comparative example using a Japanese Orihara FSM-6000LE surface stress meter; (2) Glass transition temperature T g The determination was performed in accordance with standard ASTM E-228. (3) Annealing temperature T of glass a Glass melting temperature T m The strain temperature T of the glass st The determination was carried out in accordance with the standard ASTM C-336; (4) Determination of Vickers hardness of glass: The determination shall be carried out in accordance with the standard GB / T4340.4-2022.

[0056] Examples 1-4 Examples 1-4 are glasses prepared with different raw material ratios, the difference being the different amounts of each component, as shown in Table 1.

[0057] Comparative Example 1 Comparative Example 1 is based on Example 1, except that the amount (weight percentage) of each component is different, as shown in Table 1 (unit: %).

[0058] Furthermore, formula A is defined as 0.31SiO2-0.45Al2O3, and formula B is defined as (1.35B2O3+0.72MgO) / 0.45Al2O3; in the above formulas A and B, "SiO2", "B2O3", "MgO" and "Al2O3" respectively refer to the weight percentage (unit: %) of the corresponding components in each embodiment or comparative example.

[0059] Table 1

[0060] As shown in Table 1, the content of boron oxide component in Comparative Example 1 is 0, which does not meet the component requirements of this invention. Correspondingly, the B value of 0.28 in Comparative Example 1 also does not meet the requirements of this invention for the range of B values.

[0061] The preparation process of Examples 1-4 and Comparative Example 1 is the same, specifically including the following steps: S10. Based on the designed glass composition, calculate the required raw materials, mix them thoroughly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, using a 1:1 weight ratio of NaNO3 and CeO2, with the clarifying agent added at 0.5 wt% of the raw materials. The melting temperature T corresponding to the components in each embodiment or comparative example is... m Heat for 7 hours and mix evenly. Remove the crucible and pour the molten glass into a preheated mold to form a block. Place the formed glass block in a muffle furnace and hold at the annealing temperature for 2 hours. Cool to room temperature and remove. S20. Cut the glass intermediate obtained in step S10 to obtain a glass plate intermediate; control the thickness of the glass plate intermediate to be 0.6 mm. S30. The intermediate glass plate obtained in step S20 is kept at 300°C for 30 minutes. The intermediate glass plate after heat treatment is placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400°C and the chemical strengthening time is controlled at 4 hours. The molten salt includes 1 wt% NaNO3 and 99 wt% KNO3. Glass is obtained after chemical strengthening.

[0062] Performance testing: The glass transition temperatures T of the glasses prepared in Examples 1-4 and Comparative Example 1 were measured respectively. g Annealing temperature T a Melting temperature T m and strain temperature T st The surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness of the glasses prepared in Examples 1-4 were measured respectively; M was set as (T a -T st ) / (T a -T g The measurement results are shown in Table 2.

[0063] Table 2

[0064] Analysis of Table 2 shows that the T measured in Comparative Example 1... a =563℃, T g =536℃, T st =520, M=1.41; correspondingly, the measured CS value was 805.6MPa, the measured DOL value was 40.1μm, and the measured Vickers hardness after strengthening was 680HV, all of which were significantly lower than the corresponding properties measured in Examples 1-4.

[0065] Examples 5-10 Examples 5-10 are glasses prepared with different raw material ratios, the difference being the different amounts of each component, as shown in Table 3 (unit: %).

[0066] The differences between Examples 5-10 and Examples 1-4 include: 1. Different component ratios; 2. Different glass thicknesses, 0.6 mm in Examples 1-4 and 0.5 mm in Examples 5-10.

[0067] Furthermore, formula A is defined as 0.31SiO2-0.45Al2O3, and formula B is defined as (1.35B2O3+0.72MgO) / 0.45Al2O3; in the above formulas A and B, "SiO2", "B2O3", "MgO" and "Al2O3" respectively refer to the weight percentage (unit: %) of the corresponding components in each embodiment or comparative example.

[0068] Table 3

[0069] The preparation process for Examples 5-10 is the same, specifically including the following steps: S10. Based on the designed glass composition, calculate the required raw materials, mix them thoroughly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, using a 1:1 weight ratio of NaNO3 and CeO2, with the clarifying agent added at 0.5 wt% of the raw materials. The melting temperature T corresponding to the components in each embodiment or comparative example is... m Heat for 7 hours and mix evenly. Remove the crucible and pour the molten glass into a preheated mold to form a block. Place the formed glass block in a muffle furnace and hold at the annealing temperature for 2 hours. Cool to room temperature and remove. S20. Cut the glass intermediate obtained in step S10 to obtain a glass plate intermediate; control the thickness of the glass plate intermediate to be 0.5 mm. S30. The intermediate glass plate obtained in step S20 is kept at 300°C for 30 minutes. The intermediate glass plate after heat treatment is placed in molten salt for chemical strengthening treatment, and the chemical strengthening temperature is controlled at 400°C and the chemical strengthening time is controlled at 4 hours. The molten salt includes 1 wt% NaNO3 and 99 wt% KNO3. Glass is obtained after chemical strengthening.

[0070] Performance testing: The glass transition temperature T of the glasses prepared in Examples 5-10 was measured respectively. g Annealing temperature T a Melting temperature T m and strain temperature T st The surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness of the glasses prepared in Examples 5-10 were measured respectively; M was set as (T a -T st ) / (T a -T gThe measurement results are shown in Table 4.

[0071] Table 4

[0072] By comparing the measurement results in Table 4 with those in Table 2, it can be seen that the glass in Examples 5-10 is thinner than that in Examples 1-4, and the glass in Examples 5-10 has a larger CS value, higher hardness, and smaller DOL.

[0073] Examples 11-17 Examples 11-17 are based on Example 1, with the difference being that the enhanced processing technology is different, as detailed in Table 5.

[0074] Table 5

[0075] The preparation process of Examples 11-17 specifically includes the following steps: S10. Based on the glass composition of Example 1, calculate the required raw materials, mix them evenly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, using NaNO3 and CeO2 in a 1:1 weight ratio, at 0.5 wt% of the raw materials. Heat at 1520°C for 7 hours and mix evenly. Remove the crucible, pour the molten glass into a preheated mold to form a block, and place the formed glass block in a muffle furnace at the annealing temperature for 2 hours. Cool to room temperature and remove. S20. Cut the glass intermediate obtained in step S10 to obtain a glass plate intermediate; control the thickness of the glass plate intermediate to be 0.6 mm. S30. Place the intermediate glass plate obtained in step S20 at 300℃ for 30 minutes; place the intermediate glass plate after heat treatment in molten salt for chemical strengthening treatment. The chemical strengthening temperature, chemical strengthening time and molten salt composition ratio are shown in Table 5; glass is obtained after chemical strengthening.

[0076] Performance testing: The surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness of the glasses prepared in Examples 11-17 were measured respectively. The results are shown in Table 6.

[0077] Table 6

[0078] Analysis of Table 6 shows that the surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness values ​​of glass with the same composition obtained under different chemical strengthening processes vary considerably.

[0079] Examples 18-21 Examples 18-21 are based on Example 1, with the difference being that the thickness of the intermediate glass plate is different in step S20 of the preparation method, as shown in Table 7.

[0080] Comparative Examples 2-5 Comparative Examples 2-5 are based on Comparative Example 1, with the difference being that the thickness of the intermediate glass plate is different in step S20 of the preparation method, and correspondingly, the chemical strengthening time is also different; see Table 7 for details.

[0081] The preparation processes of Examples 18-21 and Comparative Examples 2-5 specifically include the following steps: S10. Calculate the required raw materials according to the glass composition in Example 1 or Comparative Example 1, mix them evenly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, using NaNO3 and CeO2 in a 1:1 weight ratio, with the clarifying agent added at 0.5 wt% of the raw materials. Heat at 1520°C or 1512°C for 7 hours and mix evenly. Remove the crucible, pour the molten glass into a preheated mold, and cast it into a block. Place the formed glass block in a muffle furnace and hold it at the annealing temperature for 2 hours. Cool to room temperature and remove. S20. Cut the glass intermediate obtained in step S10 to obtain a glass plate intermediate; control the thickness of the glass plate intermediate to the thickness corresponding to Table 7. S30. Place the intermediate glass plate obtained in step S20 at 300℃ for 30 minutes; place the intermediate glass plate after heat treatment in molten salt for chemical strengthening treatment, control the chemical strengthening temperature at 400℃, and the specific chemical strengthening time is shown in Table 7; the molten salt includes 1 wt% NaNO3 and 99 wt% KNO3; after chemical strengthening, glass is obtained.

[0082] Performance testing: The surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness of the glasses prepared in Examples 18-21 and Comparative Examples 2-5 were measured respectively. The results are shown in Table 7.

[0083] Table 7

[0084] Analysis of the data in Table 7 shows that the surface stress intensity (CS), surface stress depth (DOL), and Vickers hardness value all change significantly with the thickness of the glass. The glass prepared in Example 1 of this invention has a CS value of 603 MPa even when the thickness is only 0.05 mm, indicating that it has good surface stress intensity.

[0085] Analysis of the data in Tables 1-7 shows that the glass prepared in this invention has a melting temperature (Tm) of 1520℃~1600℃ and a glass Tm of [missing information].a Annealing temperature ≥570℃, glass T g Transition temperature ≥550℃, glass T st The strain temperature is ≥535℃; the surface stress strength (CS) of the chemically strengthened glass obtained by this invention is >425MPa, the surface stress depth (DOL) is >12μm, and the strengthening hardness is >600HV.

[0086] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A glass, characterized in that: The glass comprises the following components by weight percentage: Silicon dioxide: 61-66wt%; Alumina: 12-20wt%; Boron oxide: 2-5wt%; Sodium oxide: 10-16wt%; Potassium oxide: 0.5~3wt%; Magnesium oxide: 0.5~4wt%; Wherein, the weight relationship between the silicon dioxide and aluminum oxide satisfies: 9.91≤0.31SiO2-0.45Al2O3≤15.06; And / or, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide satisfies: 0.34≤(1.35B2O3+0.72MgO) / 0.45Al2O3≤1.

78.

2. The glass according to claim 1, characterized in that In the components of the glass, the weight relationship between the silicon dioxide and aluminum oxide satisfies: 13.44≤0.31SiO2-0.45Al2O3≤15.06; And / or, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide satisfies: 1.13≤(1.35B2O3+0.72MgO) / 0.45Al2O3≤1.

78.

3. The glass according to claim 1, characterized in that In the components of the glass, the weight relationship between the silicon dioxide and aluminum oxide satisfies: 9.91≤0.31SiO2-0.45Al2O3≤12.35; And / or, the weight relationship of the aluminum oxide, boron oxide and magnesium oxide satisfies: 0.34≤(1.35B2O3+0.72MgO) / 0.45Al2O3≤0.

84.

4. The glass according to claim 1, wherein The annealing temperature of the glass is T a , glass transition temperature T g and strain temperature T st The following relations are satisfied: 1.65≤(T a -T st ) / (T a -T g )≤3.5。 5. The glass according to claim 1, wherein: The melting temperature of the glass is T m 1520~1600℃; and / or, the annealing temperature of the glass a >570℃; And / or, the glass transition temperature T g ≥550℃; and / or, the strain temperature T of the glass st ≥535℃.

6. The glass according to claim 1, wherein: When the thickness of the glass is 0.5-0.6 mm, the stress strength CS value of the glass is 903-942 MPa; And / or, when the thickness of the glass is 0.5-0.6 mm, the stress layer depth DOL value of the glass is 39.8-45.1 μm; And / or, when the thickness of the glass is 0.5-0.6 mm, the Vickers hardness value of the glass is 710-747 HV.

7. A method for preparing the glass according to any one of claims 1 to 6, characterized in that: The method for preparing the glass comprises the following steps: S10, mixing, melting, clarifying, homogenizing, molding, and annealing the components in the raw materials according to a proportion to obtain a glass intermediate; S20, cutting the glass intermediate product obtained in step S10 to obtain a glass plate intermediate product; controlling the thickness of the glass plate intermediate product to be 0.02-0.6 mm; S30, chemically strengthening the glass plate intermediate product obtained in step S20 to obtain the glass.

8. The method for preparing glass according to claim 7, characterized in that: The chemical strengthening in step 30 specifically includes: The glass plate intermediate product obtained in step 20 is kept at 270-320° C. for 30-50 minutes, and then the glass plate intermediate product after the heat preservation treatment is placed in molten salt for chemical strengthening treatment, and the chemical strengthening temperature is controlled to be 400-430° C., and the chemical strengthening time is controlled to be 0.25-4 hours.

9. The method for preparing glass according to claim 8, characterized in that: The molten salt includes 0-1 wt% of NaNO3 and 99-100 wt% of KNO3.

10. A display device, characterized in that: The display device uses the glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Alkaline aluminosilicate protective glass capable of realizing ion exchange and preparation method thereof

    CN106698928A

  • Aluminosilicate glass and preparation method thereof

    CN108706867A

  • High aluminosilicate glass as well as preparation method and application thereof

    CN116282909A

  • Aluminosilicate glass, tempered glass, glass structure, preparation method and application

    CN117263518A

  • Aluminosilicate glass, preparation method thereof and glass product

    CN119100587A